Self-Reported Vision Impairment and Frailty among Older People with Low Cognitive Performance in Central Africa: EPIDEMCA Population-Based Study - Gbessemehlan, A; HOUINATO, Dismand (My University, 2021)
Abstract Introduction: Very little is known about the impact of vision impairment (VI) on physical health in late-life in sub-Saharan Africa populations, whereas many older people experience it. We investigated the association between self-reported VI and frailty in Central African older people with low cognitive performance. Methods: It was cross-sectional analysis of data from the Epidemiology of Dementia in Central Africa (EPIDEMCA) population-based study. After screening for cognitive impairment, older people with low cognitive performance were selected. Frailty was assessed using the Study of Osteoporotic Fracture index. Participants who met one of the 3 parameters assessed (unintentional weight loss, inability to do 5 chair stands, and low energy level) were considered as pre-frail, and those who met 2 or more parameters were considered as frail. VI was self-reported. Associations were investigated using multinomial logistic regression models. Results: Out of 2,002 older people enrolled in EPIDEMCA, 775 (38.7%) had low cognitive performance on the screening test. Of them, 514 participants (sex ratio: 0.25) had available data on VI and frailty and were included in the analyses. In total, 360 (70%) self-reported VI. Prevalence of frailty was estimated at 64.9% [95% confidence interval: 60.9%–69.1%] and 23.7% [95% CI: 20.1%–27.4%] for pre-frailty. After full adjustment, self-reported VI was associated with frailty (adjusted odds ratio = 2.2; 95% CI: 1.1–4.3) but not with pre-frailty (adjusted odds ratio = 1.8; 95% CI: 0.9–3.7). Conclusion: In Central African older people with low cognitive performance, those who self-reported VI were more likely to experience frailty. Our findings suggest that greater attention should be devoted to VI among this vulnerable population in order to identify early frailty onset and provide adequate care management.
Keywords: Fraitly; population-based study; African older people